Implementasi Teknologi Hilirisasi Biokonversi Limbah Baglog Menjadi Kompos pada Kelompok Wanita Tani Limau Manis Sejahtera Di Kecamatan Pauh Kota Padang: Implementation Of Downstream Technology For Converting Spent Mushroom Baglog Waste Into Compost For The Limau Manis Sejahtera Women Farmers Group In Pauh District, Padang City - Fiana, Risa Meutia; Asben, Alfi; Murtius, Wenny Surya; Koja, Reni; Febjislami, Shalati; Syukri, Daimon; Novelina, Novelina (Jurnal Hilirisasi IPTEKS, 2026)
The utilization of sawdust waste in the early stages of mushroom cultivation represents an effort to support environmental conservation. However, challenges arise when the growing media becomes non-productive and remains underutilized. Accumulated baglog waste may serve as a reservoir for spore development, with the potential for airborne dispersion or transfer via workers’ clothing. Such conditions can trigger contamination within inoculation rooms, degrade media quality, and ultimately lead to cultivation failure. In addition, improper disposal practices, such as open dumping or burning, may contribute to environmental pollution and reduced sustainability of mushroom farming systems. Bioconversion technology offers a viable solution by transforming baglog waste into value-added products, including compost. Program components consisted of instructional delivery through an extension session on baglog waste bioconversion and hands-on practice in composting procedures. Practical implementation was supervised by the facilitation team to ensure participants’ comprehension and skill acquisition in processing non-productive baglog waste. The participatory approach enabled active engagement of participants throughout the program. Program implementation demonstrated an improvement in participants’ knowledge and technical competencies, particularly among members of the Limau Manis Sejahtera Women Farmers Group, in converting oyster mushroom baglog waste into compost. Participants successfully understood the composting stages and were able to independently apply the procedures. Baglog waste that was previously discarded or burned was effectively converted into compost, generating added value while simultaneously supporting environmentally sustainable agricultural practices.